Akuntabilitas dan Transparansi Pengelolaan Keuangan pada Yayasan Panti Asuhan Attafakur - Berlina Yudha Pratiwi; Fitria Abroril Iliyin (Politeknik Negeri Jember, 2023)
This study aims to determine and explain the accountability and transparency of financial management at the Attafakur orphanage foundation. The research method used is a qualitative method using primary and secondary data, namely the results of interviews and documentation. To test the validity of the data using source triangulation techniques and technical triangulation. The results of this study explain that the Attafakur Orphanage Foundation has implemented the principles of accountability and transparency in its financial management. However, there are still several obstacles, namely a lack of human resources related to recording receipts from donors in the form of goods.